Electrical resistivity and flexural strength of plastic composites reinforced with pineapple leaf particles / Shahril Anuar Bahari ... [et al.] - Bahari, Shahril Anuar; Yahya, Mohd Khairi; Abu Kassim, Masitah; Muhammad, Khairul Safuan; Baharom, Rahimi (Research Management Institute (RMI), 2011)
The electrical resistivity and flexural strength of plastic composites reinforced with pineapple leaf particles (PCPLP) is presented. PCPLP were produced using different plastic materials; Polyethylene (PE) and Polypropylene (PP), and different plastic-pineapple leaf particle ratios; 50:50 and 70:30. The PCPLP were tested and evaluated with respect to electrical resistivity and flexural strength according to ASTM D257 and D790, respectively. The results indicate that PCPLP made from PP exhibits better electrical resistance than PE, which may be attributed to the better frequency insulation behaviour of PP. PCPLP using the higher ratio of 70:30 also exhibited better electrical resistance than the lower 50:50 ratio. Cellulose materials inherently influence the electrical resistance of plastic composites, due to their natural propensity to absorb moisture. The PCPLP produced using a ratio of 50:50 for both PP and PE composites exhibited better MOE results than the 70:30 composites, however the converse is true with respect to the MOR. MOE of PCPLP was increased with increasing pineapple leaf particles content due to the greater matrix stiffness of this natural particle with respect to plastic matrix. However, high percentage of filler particles in the matrix (70:30 ratio) has reduced the toughness in the composite structure due to the lost of physical contact between high accumulated particles.